Variation of Lightning Activity Over Parts of the Western Coast of Africa - (:unkn) unknown (My University, 2024)
This study examines the variation of lightning activity along the western coast of Africa using experimental VLF-WWLLN data collected over a five-month period in 2011. A total of 3,885 lightning strokes were analyzed across five geographical regions, spanning from southeastern Ghana to northeastern parts of the Democratic Republic of Congo. The results reveal substantial variability in lightning activity, with southeastern Ghana and southern Togo (Location A) showing consistently high activity levels, except for a marked decline in September. The region covering southern Nigeria and Cameroon (Location C) exhibited the highest peak in lightning activity in September, accounting for over 41% of total strokes that month. Conversely, the region encompassing parts of the Central African Republic and South Sudan (Location E) recorded the lowest activity throughout the study period. Seasonal trends indicate heightened lightning occurrences during the rainy season, with significant spikes in August and September across several regions. The findings offer critical insights into regional lightning dynamics, emphasizing areas prone to intense activity and temporal variations that align with seasonal weather patterns. These results are vital for enhancing lightning risk management, informing infrastructure design to mitigate damage, and contributing to the development of climate models for understanding atmospheric processes in coastal West Africa.
Keywords: African Research